Colonialism as an organizational development strategy : case studies on donor-dependent organisations in Haiti and the Commonwealth Caribbean. - HUFF-ROUSSELLE, Maggie (1992)
Examines how the development of donor-dependent organisations are influenced by their donors. Explores why this influence occurs.